Modifikasi Alat Kuat Tekan Paving Block Sebagai Alat Cetak Hidrolik - Andy Eka Saputra (Jurnal Ilmiah Teknik Pertanian - TekTan, 2020)
The Paving Block industry is one of the important industries, as a driving force for the economy of an area, one of which is in Bandar Lampung, especially in the Rajabasa district. The problem that is often faced by consumers is the low quality of the paving that is used, which is often cracked, broken and brittle so that it interferes with all the activities carried out in the paving block application in use, this is due to the quality of the materials that do not meet standards and the manufacturing process is not quite right. The objectives of this research are to test the performance of the modified molding tools and test the paving blocks produced using the tools before modification with those that have been modified. Based on the results of research conducted at the Lampung State Polytechnic in 2019 for 6 months, it shows that the compressive strength of paving block molded steel plates with a side length of 20 cm, a width of 6 cm and a height of 8 cm with a plate thickness of 5 mm can withstand existing leaks and can be used. with hydraulic molding equipment modified on the CTM machine. In the print results with a pressure of 50 kg / cm2, no leaks were found on the printing machine and at a pressure of 100 kg/cm2, the printing press was still able to withstand the leak, so it could be used as a printing tool in the modification of hydraulic molding devices on the CTM machine. Modification of paving block formers provides paving block results with class B quality according to the Indonesian National Standard Agency, 1996.Â Keywords: paving block, modified compressive strength, steel plates